Immunotherapeutic potential of mutated NPM1 for the treatment of acute myeloid leukemia - Greiner, Jochen; Mohamed, Eithar; Fletcher, Daniel M.; Schuler, Patrick; Schrezenmeier, Hubert; Götz, Marlies; Guinn, Barbara (Cancers, 2024)
Acute myeloid leukemia (AML) is a malignant disease of the blood and bone marrow that is characterized by uncontrolled clonal proliferation of abnormal myeloid progenitor cells. Nucleophosmin 1 (NPM1) gene mutations are the most common genetic abnormality in AML, detectable in blast cells from about one-third of adults with AML. AML NPM1mut is recognized as a separate entity in the World Health Organization classification of AML. Clinical and survival data suggest that patients with this form of AML often have a more favorable prognosis, which may be due to the immunogenicity created by the mutations in the NPM1 protein. Consequently, AML with NPM1mut can be considered an immunogenic subtype of AML. However, the underlying mechanisms of this immunogenicity and associated favorable survival outcomes need to be further investigated. Immune checkpoint molecules, such as the programmed cell death-1 (PD-1) protein and its ligand, PD-L1, play important roles in leukemogenesis through their maintenance of an immunosuppressive tumor microenvironment. Preclinical trials have shown that the use of PD-1/PD-L1 checkpoint inhibitors in solid tumors and lymphoma work best in novel therapy combinations. Patients with AML NPM1mut may be better suited to immunogenic strategies that are based on the inhibition of the PD-1 immune checkpoint pathway than patients without this mutation, suggesting the genetic landscape of patients may also inform best practice for the use of PD-1 inhibitors.
Gesehen am 07.04.2025